Adipocyte Xbp1s overexpression drives uridine production and reduces obesity - Yingfeng Deng; Zhao V. Wang; Ruth Gordillo; Yi Zhu; Aktar Ali; Chen Zhang; Xiaoding Wang; Mengle Shao; Zhuzhen Zhang; Puneeth Iyengar; Rana K. Gupta; Jay D. Horton; et al. (Elsevier, 2018)
Objective: The spliced transcription factor Xbp1 (Xbp1s), a transducer of the unfolded protein response (UPR), regulates lipolysis. Lipolysis is stimulated by fasting when uridine synthesis is also activated in adipocytes. Methods: Here we have examined the regulatory role Xbp1s in stimulation of uridine biosynthesis in adipocytes and triglyceride mobilization using inducible mouse models. Results: Xbp1s is a key molecule involved in adipocyte uridine biosynthesis and release by activation of carbamoyl-phosphate synthetase 2, aspartate transcarbamylase, dihydroorotase (CAD), the rate-limiting enzyme for UMP biosynthesis. Adipocyte Xbp1s overexpression drives energy mobilization and protects mice from obesity through activation of the pyrimidine biosynthesis pathway. Conclusion: These observations reveal that Xbp1s is a potent stimulator of uridine production in adipocytes, enhancing lipolysis and invoking a potential anti-obesity strategy through the induction of a futile biosynthetic cycle. Keywords: Obesity, Xbp1, ER stress, UPR, Pyrimidine, Uridine, CAD